Perlawanan perempuan yang terpinggirkan dalam Novel “Anak Semua Bangsa” Karya Paramodya Ananta Toer - Nensilianti, Nensilianti; Ridwan, Ridwan; Ramadhan, Nur Syawaluddin (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research aims to analyze the novel "Children of All Nations" by Pramoedya Ananta Toer in the context of the struggle of oppressed women in Dutch colonial society. This analysis uses a feminist approach, focusing on the resistance of marginalized women. This research uses a qualitative descriptive methodology, where reading and note-taking techniques are applied in the data collection process. Reading techniques are used to understand and interpret the content of the text, while note-taking techniques focus on female characters in the novel who experience various types of gender-based oppression and injustice. The results of text analysis show that in the patriarchal culture of the Dutch East Indies colonial era, indigenous women figures such as Nyai Ontosoroh aggressively resisted oppression and fought for the rights of women who were always oppressed and marginalized. This research found that women are often marginalized and disadvantaged in societies dominated by men since the colonial era. In conclusion, it is hoped that the findings of this research will help to better understand the resistance of marginalized women in historical and social contexts.Keywords: Feminism, Resistance, Marginalized